Social media as an English learning platform during the pandemic - Nida Husna; Yatni Fatwa Mulyati; Nur Aisyah Karim; Didin Nuruddin Hidayat; Muhammad Farkhan; Alek Alek (UPT Bahasa Universitas Tanjungpura, 2022)
Online learning is not always about using learning platforms explicitly designed for learning. This study aimed to reveal the students' perception of using one social media as the primary learning platform in an extensive reading subject as one of the language learning strategies. This case study used open-ended questionnaires and semi-structured interviews as the instruments to gather the data. There were 64 students (52 females and 12 males) from three classes and a lecturer, chosen using purposive sampling as the participants. The findings showed that the use of Facebook as one of the social media platforms for online learning was considerably effective and satisfying, and the students' questionnaire results and lecturer interviews revealed that Facebook has easy-to-use features and could be used as communication media. This study suggests that educators were expected to start broadening the use of their social media applications so those can also be used as platforms for their teaching activities in the classroom.